Amortiguamiento en transductores de ultrasonido de película gruesa - Gwirc, S. (2006)
The piezoelectric pastes to be used in thick film technology for ultrasound transducers present lower acoustic impedance than the traditional bulk ceramic, allowing an enhancement in the coupling transducer-tissue. In this work we present an alternative to diminish the acoustic impedance, adding another layer to the thick film structure of the ultrasound transducer and the behavior of the emitted signal is analyzed. The addition of a glass layer with tungsten to the piezoelectric transducers, allowed approaching its impedance to that of the resin that which is a considerable improvement in the acoustic response of the transducer. In this way it can be considered the thickness and the active load of the layers to achieve the acoustic attenuation in the backing.